Review of Bladder Pain and Referred T12–L2 Input as One Etiology for Interstitial Cystitis - Dellon, A. Lee; Herati, Amin S. (Journal of Reconstructive Microsurgery Open, 2019)
Background The etiology of interstitial cystitis (IC)/bladder pain syndrome (BPS) remains a mystery. Based on two patients, whose IC/BPS was relieved by resection of injured iliohypogastric (IH) and ilioinguinal (II) nerves, injured by endoscopic prostatectomy in the first patient and a stretch/traction injury in the second patient, a referred pain pathway is hypothesized that can be applied to patients with IC/BPS and previous abdominal wall surgery/injury.Methods The known neurophysiology of bladder function was reviewed as were the pathways for accepted referred pain syndromes.Results Perception of bladder filling occurs by impulses generated from stretch receptors in the bladder wall, traveling along visceral afferent fibers that enter the thoracolumbar spinal cord at T12, L1, and L2, the same location as the sympathetic outflow to the viscera and the same location as some of the visceral afferents from the bladder. The II and IH nerves originate from T12, L1, and sometimes L2 somatic, dorsal root ganglia. It is hypothesized that somatic afferent pain impulses, from the lower abdominal wall, are misinterpreted as visceral afferent impulses from the bladder, giving rise to the urinary frequency and urgency of IC/BPS. Resecting injured cutaneous afferents (II and IH) permitted long-term IC/BPS relief in the first patient for 59 months and in the second patient for 30 months. Neural inputs from the sacral visceral afferents and sacral somatic afferents did not appear to be involved in this referred pain pathway.Conclusion Nerve blocks of the T12 -L2 spinal nerves in patients with bladder pain who also have had abdominal wall surgery/injury may identify IC/BPS patients for whom resection of the II and IH nerves may prove beneficial in obtaining lasting IC/BPS relief.
Keywords: bladder pain; ilioinguinal; iliohypogastric